Implementation of Scalar Control Technique in SVPWM Switched Three–Level Inverter Fed Induction Motor Using DSP Controller - Vinoth Kumar; S. Suresh Kumar; Kishore Reddy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2011)
The main objective of the paper is to control the speed of an induction machine with scalar control technique. The scalar control technique (V/F) is used because of simplicity of control algorithm implementation and the response is better and accurate with closed loop slip compensation. An IGBT based three level diode clamped inverter (DCI) topology has been used instead of conventional two level inverter in order to reduce the harmonic content and to increase the device capability to handle the double the voltage of its rating.DOI: http://dx.doi.org/10.11591/ijpeds.v1i2.98